From Literal Meaning to Emotional Expressions: A Semantic Change of Emotional Slangs in Tiktok Comments - Wefi putri dabhita; Dedy Subandowo; Bambang Eko Siagiyanto (Lingual: Journal of Language and Culture, 2026)
This study examines the semantic changes and emotional functions of emotional slang in TikTok comments from 2024 to 2025. Using a qualitative descriptive approach, five TikTok comments were analyzed using Ullmann's semantic change theory and Martin and White's Evaluation Theory. The results show that slang undergoes systematic semantic processes, such as amelioration, pejoration, and widening, which transform literal meanings into emotional expressions. These emotional meanings function in the domains of Affect, Judgment, and Appreciation, enabling users to express personal feelings, evaluate behavior, and convey admiration. This study concludes that semantic change in emotional slang is a socially driven process that strengthens emotional expression and interpersonal communication in digital discourse.